Catheter ablation of ventricular tachycardia in nonischemic cardiomyopathy: A propensity score‐matched analysis of in‐hospital outcomes in the United States. (9th March 2018) - Briceño, David F.; Gupta, Tanush; Romero, Jorge; Kolte, Dhaval; Khera, Sahil; Villablanca, Pedro A.; Tran, An; Mohanty, Sanghamitra; Trivedi, Chintan; Mohanty, Prasant; Gianni, Carola; Kim, Soo G.; et al.
Abstract: Introduction: Monomorphic ventricular tachycardia (VT) is an important cause of morbidity and mortality. Use and outcome data of catheter ablation for VT in nonischemic cardiomyopathy (NICM) are limited. Methods and results: We obtained data from the 2003–2014 National Inpatient Sample databases. We used propensity score matching to compare patients undergoing catheter ablation versus medical therapy of VT related to NICM, and described the temporal trends in utilization and in‐hospital outcomes of catheter ablation of VT in patients with NICM in the United States. From 2003 to 2014, of 133, 529 patients hospitalized with the principal diagnosis of VT in NICM, 14, 651 (11.0%) underwent catheter ablation. In this period, there was an increasing trend in utilization of catheter ablation (9.3% in 2003–2004 to 12.1% in 2003–2014, adjusted OR [per year], 1.12; 95% CI, 1.08–1.16; Ptrend < 0.001). After propensity score matching, in‐hospital mortality occurred in 172 of 14, 318 (1.2%) patients in the catheter ablation group, compared with 297 of 14, 156 (2.1%) of patients undergoing medical therapy (47% lower; 43% relative difference [adjusted OR, 0.53; 95% CI, 0.43–0.66]). Conclusions: In patients with NICM, catheter ablation of VT is associated with lower in‐hospital mortality compared with those managed medically. The utilization rates of CA for VT related to NICM have increased in the past decade. Adequately powered randomized trials will be necessary to confirm these findings.